Enriched environment provides neuroprotection against experimental glaucoma - González Fleitas, María Florencia (2019)
Glaucoma is one of the most frequent causes of visual impairment worldwide, and involves selective damage to retinal ganglion cells (RGCs) and their axons. We analyzed the effect of enriched environment (EE) housing on the optic nerve, and retinal alterations in an induced model of ocular hypertension. For this purpose, male Wistar rats were weekly injected with vehicle or chondroitin sulfate (CS) into the eye anterior chamber for 10 weeks and housed in standard environment or EE. EE housing prevented the effect of experimental glaucoma on visual evoked potentials, retinal anterograde transport, phosphorylated neurofilament-immunoreactivity, axon number, microglial/macrophage reactivity (ionized calcium binding adaptor molecule 1-immunoreactivity), and astrocytosis (glial fibrillary acidic protein-immunostaining), as well as oligodendrocytes alterations (luxol fast blue staining, and myelin basic protein-immunoreactivity) in the proximal portion of the optic nerve. Moreover EE prevented the increase in ionized calcium binding adaptor molecule-1 levels, and RGC loss (Brn3a-immunoreactivity) in the retina from hypertensive eyes. EE increased retinal brain-derived neurotrophic factor levels. When EE housing started after 6 weeks of ocular hypertension, a preservation of visual evoked potentials amplitude, axon, and Brn3a(+) RGC number was observed. Taken together, these results suggest that EE preserved visual functions, reduced optic nerve axoglial alterations, and protected RGCs against glaucomatous damage.